Education & society in aotearoa new zealand : an introduction - Codd, John.; Adams, Paul.; Clark, John.; O'Neill, Anne-Marie.; Openshaw, Roger; Waitere-Ang, Hine. ([S.l.] : Dunmore Press, 2000)
Why do some children fail at school while others succeed? What role do gender and ethnicity play in education? Can teachers really make a difference? Who should decide what is in the curriculum? Why do we have exams? Beginning with a broad introduction to the nature of society, and what schools are for, this timely book goes on to consider the hidden, and not so hidden, structures and processes of education. After examining various ongoing struggles over curriculum, credentialling and administration, it concludes by analyzing a range of theories which purport to explain differences in educational achievement. This book has been designed for students studying education for the first time, for those involved in education in various areas (such as teachers aides and members of Boards of Trustees) and will be of particular interest to parents who would like to ensure their children's educational success. It is essential reading for those wishing to understand fully the relationship between education and society in Aotearoa New Zealand.
Keywords: Education and state; Education--Social aspects; Multicultural education; New Zealand